2019
DOI: 10.1037/pspa0000141
|View full text |Cite
|
Sign up to set email alerts
|

The physiological basis of psychological disgust and moral judgments.

Abstract: To address ongoing debates about whether feelings of disgust are causally related to moral judgments, we pharmacologically inhibited spontaneous disgust responses to moral infractions and examined effects on moral thinking. Findings demonstrated, first, that the antiemetic ginger (Zingiber officinale), known to inhibit nausea, reduces feelings of disgust toward nonmoral purity-offending stimuli (e.g., bodily fluids), providing the first experimental evidence that disgust is causally rooted in physiological nau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 67 publications
3
40
0
Order By: Relevance
“…As people who were less hungry reported to have eaten more recently, a "fullness"-based explanation is perhaps more likely and is consistent with some prior research (Vicario et al, 2018). Nausea symptoms often correlate with post-eating gastric emptying (Halawi et al, 2017) and can be interpreted emotionally as disgust (Tracy et al, 2019), which can influence moral judgments (see Haidt et al, 1994). However, this is a novel finding for harm-based moral judgments (Horberg et al, 2009).…”
Section: Hunger and Moral Acceptability Ratingsmentioning
(Expert classified)
See 1 more Smart Citation
“…As people who were less hungry reported to have eaten more recently, a "fullness"-based explanation is perhaps more likely and is consistent with some prior research (Vicario et al, 2018). Nausea symptoms often correlate with post-eating gastric emptying (Halawi et al, 2017) and can be interpreted emotionally as disgust (Tracy et al, 2019), which can influence moral judgments (see Haidt et al, 1994). However, this is a novel finding for harm-based moral judgments (Horberg et al, 2009).…”
Section: Hunger and Moral Acceptability Ratingsmentioning
(Expert classified)
“…A dispositional sensitivity toward feelings of disgust was also found to increase the severity of moral disapproval ratings of ethical violations. Vicario and colleagues suggested hormonal reactions and interoceptive signals triggered by eating may evoke feelings of nausea interpreted as disgust (Tracy et al, 2019), which subsequently inform moral judgments. This is consistent with other work (Wheatley and Haidt, 2005;Horberg et al, 2009), including Schnall et al (2008), who found disgust manipulations encourage harsher judgments of ethical violations and is strongest for those with a greater tendency to pay attention to interoceptive sensations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a large body of research links the emotion of disgust with judgments of moral wrongness (e.g. Eskine, Kacinik, & Prinz, 2011; Tracy, Steckler, & Heltzel, 2019; Tybur, Lieberman, Kurzban, & DeScioli, 2013), especially in the sanctity domain (Wagemans, Brandt, & Zeelenberg, 2018), which according to the Moral Foundations Theory captures moral intuitions about transgressing physical and spiritual purity (Graham et al, 2013). Moreover, sensory and moral disgust seem to share common characteristics on both neural and physiological levels (H. Chapman, Kim, Susskind, & Anderson, 2009; Vicario et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For this analysis, we examined Tweets posted from June 1, 2015 to December 31, 2017, and geo-location was again limited to the U.S. We selected a broader set of keywords than above, all representing different affective expressions that could be potentially linked to political actions of representative leaders in the CH database. Keywords were affective expressions of either positive or negative valence, with some representing what have been called moral emotions (i.e., embarrassment, shame, pride, and guilt, see Tracy et al, 2007), and some affective expressions that may be considered not in this moral emotion domain (i.e., happiness, sadness, anger, and disgust, for a discussion of the moral implications of disgust however see e.g., Chapman et al, 2009;Giner-Sorolla and Chapman, 2017;Tracy et al, 2019). For each emotional expression we searched the CH database for relevant forms, such as conjugations, that could appear in written communication, similar to our search for embarrassment expressions for each day as explained above (i.e., shame: "shame" | "ashamed" | "shameful"; guilt: "guilt" | "guilty"; pride: "pride" | "proud"; embarrassment: "embarrassment" | "embarrassed" | "embarrassing" | "embarrasses"; anger: "anger" | "angry" | "angers"; happiness: "happy" | "happiness"; sadness: "sad" | "saddening" | "saddens"; disgust: "disgust" | "disgusting" | "disgusted" | "disgusts").…”
Section: Methodsmentioning
confidence: 99%